The Effect of Probing Prompting Model on Learning Outcomes of Plane Shapes Material In Grade III SDN Petok - Zakiyya, Rizan; Fajrin, Nilamsari Damayanti; Hidayat, Panji (eductum: Jurnal Literasi Pendidikan, 2025)
This study aims to determine whether or not there is a significant effect of the use of the probing prompting model on student learning outcomes in flat geometry material in class III SDN Petok, Mojo District, Kediri Regency. This study uses a quantitative method. The research design uses a pre-experimental design with a one group pretest posttest design. The population in this study were all third-grade students at SDN Petok in the 2023/2024 Academic Year. Sampling used a non-probability sampling technique, a saturated sampling type. The research sample was 19 students. Data were collected using observation and tests. The results showed that the magnitude of the effect was evident in the Wilcoxon test results obtained a significant value of 0.000. Based on the testing criteria, if the value of sig less than0.05 then H0 is rejected and H1 is accepted, which states that there is a difference in the pretest and posttest results. This means that there is a significant effect of the use of the probing prompting model on student learning outcomes in flat geometry material in class III SDN Petok.